Low‐Dimensional Contact Layers for Enhanced Perovskite Photodiodes. (27th April 2020) - Luo, Deying; Zou, Taoyu; Yang, Wengqiang; Xiang, Beng; Yang, Xiaoyu; Wang, Ya; Su, Rui; Zhao, Lichen; Zhu, Rui; Zhou, Hang; Russell, Thomas P.; Yu, Hongyu; et al.
Abstract: Controlling defects and energy‐band alignments are of paramount importance to the development of high‐performance perovskite‐based photodiodes. Yet, concurrent improvements in interfacial contacts and defect reduction simply by tailoring bottom contacts have not been investigated. An effective strategy is reported that can simultaneously improve energy‐band alignments and structural defects by introducing low‐dimensional contact (LDC) layers at the bottom interface. It is found that LDC‐based perovskites considerably suppress undesirable structural defects induced by microstrains, resulting in reduced nonradiative recombination centers and improved carrier lifetimes. Additionally, the resulting LDC‐based interface structures help block minority carrier injection from the electrodes by forming built‐in electric fields. As a consequence, LDC‐based perovskite photodiodes showed improved light detection capabilities. The result opens an avenue to yield highly efficient photodiodes. Abstract : Enhanced optoelectronic characteristics for perovskite photodiodes are demonstrated by tailoring the bottom interface. A phenyltrimethylammonium (or phenethylammonium)‐bromide‐based low‐dimensional contact is utilized for mitigating structural defects within the perovskite films while tuning the localized electric field near the bottom electrode. The resulting device is capable of operating in both the forward and reverse bias voltages, with enhanced device performance.